دور القصص القرآني في تدريس اللغة العربية كلغة ثانية: قصة النبي آدم عليه السلام أنموذجا: The role of Quranic stories in teaching Arabic as a second language: The story of the Prophet Adam, peace be upon him, as an example - hikmah, admin; Abdallah Sabir Mahmoud, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يدرس البحث دور القصص القرآني في تدريس اللغة العربية كلغة ثانية، مسترشدا بذلك على قصة النبي آدم عليه السلام كأنموذج يظهر من خلاله أثر القصص القرآني في تسهيل عملية التدريس بشكل عام وتدريس اللغة العربية بشكل خاص، من خلال الإثراء في المفردات والوضوح في التراكيب، فضلا عن النواحي الفكرية والثقافية بما يساهم في ترسيخ القيم والأخلاق الإسلامية، ويشجع على التفكير النقدي والتحليل وصولا إلى تحسين المهارات اللغوية المختلفة، ويهدف البحث إلى بيان مفهوم القصة القرآنية، والتعرف على خصائصها رغبة في التعرف على أهدافها وأثرها في تدريس اللغة العربية، والإسهام في تزويد معلم اللغة العربية بنماذج تساعده في ذلك، وذلك بالرجوع إلى مشكلة البحث والتي تتلخص في استخدام سرد القصة في تدريس اللغة العربية، كأسلوب من أساليب العملية التعليمية، والتي يمكن الاستفادة منها على كافة الاختصاصات وفي جميع المجالات ومنها تدريس اللغة العربية، ويعتمد البحث على المنهج الاستقرائي والمنهج والوصفي والمنهج التاريخي في عملية جمع بياناته وتحليلها وصولا إلى النتائج. ABSTRACT This research provides an overview of the benefits of the role of the Qur'anic narrative method, represented in the story of Adam (PBUH), in facilitating the process of teaching Arabic to non-Arabic speakers (Documentary Analysis). The research demonstrates that this approach encourages active participation and stimulates interest among learners. It also contributes to expanding their vocabulary and improving their language skills. Additionally, it enhances cultural and religious understanding and promotes critical thinking. This approach can also guide further reading and enhance communication with Arabic-speaking communities. In essence, presenting Quranic stories as an educational tool can be an effective and engaging means to achieve Arabic language learning goals for non-native speakers. This research explores the significance of implementing the Quranic narrative style in teaching the Arabic language to non-native speakers. The study underscores the multifaceted advantages of using Quranic stories as a pedagogical tool in Arabic language instruction.